2014
DOI: 10.1021/jp507259g
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Excited States of Bacteriochlorophyll a in Solutions with Density Functional Assessment

Abstract: The excited-state properties of bacteriochlorophyll (BChl) a in triethylamine, 1-propanol, and methanol are investigated with the time-dependent density functional theory by using the quantum mechanical and molecular mechanical reweighting free energy self-consistant field method. It is found that no prevalent density functionals can reproduce the experimental excited-state properties, i.e., the absorption and reorganization energies, of BChl a in the solutions. The parameter μ in the range-separated hybrid fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 118 publications
(265 reference statements)
3
38
0
Order By: Relevance
“…16,22,42,43 We have also shown that the electronic properties of BChl a show a strong functional dependence in DFT calculations, and thus, the use of an appropriate functional is essential for the calculation of site energies. 21 The present result shows that BChl 3 has the lowest site energy because of stable intermolecular interactions, especially the large stabilization (∼190 cm −1 ) by the hydrogen bond between Tyr15 and the acetyl group of site 3, which is consistent with the mutation experiment of Tyr to Phe, which results in an increase of the site energy by ∼170 cm −1 . 44 The present result shows that sites 2, 5, and 8 have large site energies.…”
Section: Resultssupporting
confidence: 88%
“…16,22,42,43 We have also shown that the electronic properties of BChl a show a strong functional dependence in DFT calculations, and thus, the use of an appropriate functional is essential for the calculation of site energies. 21 The present result shows that BChl 3 has the lowest site energy because of stable intermolecular interactions, especially the large stabilization (∼190 cm −1 ) by the hydrogen bond between Tyr15 and the acetyl group of site 3, which is consistent with the mutation experiment of Tyr to Phe, which results in an increase of the site energy by ∼170 cm −1 . 44 The present result shows that sites 2, 5, and 8 have large site energies.…”
Section: Resultssupporting
confidence: 88%
“…21 Furthermore, CAM-B3LYP can reproduce experimental results for excitation energies of BChl a in different solvents. 34 Using ab initio and TD-DFT approaches, excitation energies are often computed for single structures, e.g., for QM/MM optimized geometries of chromophore and protein environment. The computation of excitation energies of sampled structures obtained by molecular dynamics (MD) simulations is required not only to determine correct averages and widths of the absorption spectra, but also to investigate, e.g., temperature effects as reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…We used LC-BLYP because the correct asymptotic behaviour of the CT energy can only be reached if the amount of exact exchange is 100% at infinite separation [34]. The range-separation parameter ω was set to 0.195, a value where Qy energies are rather stable [35].…”
Section: Structure and Computational Detailsmentioning
confidence: 99%